Effect of linear and undulating training periodization models on the repeated sprint ability and strength of soccer players - Pamela R. G. Gonelli; Tiago V. Braz; Rozângela Verlengia; Ídico L. Pellegrinotti; Marcelo C. César; Márcio A. G. Sindorf; Alex H. Crisp; Marcelo S. Aoki; Charles R. Lopes (Universidade Estadual Paulista (UNESP), 2018)
Abstract Purpose: The aim of the study was to investigate the effect of linear and undulating strength-power training scheme on the repeated sprint ability (RSA) and lower body strength of soccer players. Method: Twenty soccer players (under-20 category) were split into 2 groups: the linear load (LL, n=10) and the undulating load (UL, n=10). In the commencement and at the end of the 6-week pre-season period, the RSA test (6 x 35m) and the 1RM parallel squat test (1RMsquat) were conducted. The LL and UL performed the same type and number of sessions. The training stimulus in the strength training was different between LL (Weeks 1 and 2 = Muscular Endurance; Weeks 3 and 4 = Strength; Weeks 5 and 6 = Power) and UL (daily load variation in the same week). Results: A improvement in RSAmean and 1RMsquat was detected in LL and in UL. No significant difference was noted between LL vs UL for all variables. Conclusion: Both groups improved maximal muscle strength in parallel back squat and RSA. UL induced a greater gain in RSA.